Jackpot / 6. - Korman, Gordon (Swindle, 2014)
Griffin Bing and his friends are trying to locate Mr. Fielder's missing thirty million dollar lottery ticket, and thwart the local bully, Darren Vader, who wants to find it for himself--and Mr. Bing's latest invention may help.